Analysis of Pronunciation Learning Activities in English Class at SDN 060877 through Direct Classroom Observation Techniques - Lutfiah Lutfiah; Mazaya Nazhira Alfrans; Deani Jenlionika Br Saragih; Putri Melisa Hasibuan; Eva Betty Simanjuntak (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study analyzes pronunciation learning activities in the English class at SDN 060877 through direct classroom observation techniques. The research aims to understand how teachers organize pronunciation instruction, the strategies applied during learning sessions, and the level of student participation in practicing correct sounds, stress patterns, and intonation. Using a qualitative descriptive approach, data were collected through on-site observations focusing on teaching procedures, interaction patterns, learning media, and students’ responses. The findings indicate that pronunciation learning is integrated into reading and speaking activities, where the teacher models sound, guides repetition drills, and provides corrective feedback. Students demonstrate varied levels of confidence, with some actively engaging in pronunciation tasks while others rely heavily on teacher prompts. Environmental factors, such as limited audio-media tools and large class size, affect the intensity and effectiveness of practice sessions. Despite these challenges, classroom interactions show that learners gradually improve their sound accuracy and rhythm through continuous modeling and peer practice. This study concludes that direct observation provides comprehensive insights into real classroom dynamics, revealing both the strengths and areas needing improvement in pronunciation teaching. Recommendations are offered to enhance instructional techniques, learning materials, and student engagement.